Feedback and feedforward methods in medical and higher health education: A scoping review - Jill Vögelin; Irene Koenig; Iris Sterkele; Theresa Himmelsbach; Angela Blasimann; Evert Zinzen; Slavko Rogan (PLoS ONE, 2026)
Background Programmatic assessment (PA) in health professions education positions continuous feedback and feedforward as key mechanisms for competence development. Feedback focuses on prior performance, whereas feedforward provides future-oriented guidance that supports agency and self-regulated learning. Although their educational value is widely acknowledged, implementation remains challenging and often emphasises performance outcomes rather than action and reflection. Methods A scoping review was conducted to address the research question: “How are feedback and feedforward methods operationalised within assessment situations in medical and higher health professions education? The ECLIPSE framework (Expectation, Client group, Location, Impact, Professionals, Service) guided question formulation and searches in Embase, ERIC and PubMed. Articles published from 2015 up to February 2026 were included. Data were synthesized using descriptive and thematic synthesis. The methodological quality of the included studies was assessed using Joanna Briggs Institute (JBI) critical appraisal tools. Results Database searches identified 3723 records. After deduplication and screening, 91 full texts were assessed, of which 14 studies met inclusion criteria. All studies involved medical students. Five methodological families were identified: expert feedback, self-feedback, peer feedback, video-based feedback, and feedforward. Expert and video-based approaches were consistently associated with performance gains, whereas self- and peer feedback supported reflection and learner agency but showed variable outcomes. Feedforward was rarely explicitly described, although several interventions incorporated forward-looking elements targeting performance. Conclusion Current assessment practices rely on a limited set of recurring methods, with feedforward, predominantly focused on performance, often remaining implicit. Making feedforward explicit and actionable within assessment cycles might strengthen competence development, promote learner agency, and support continuous improvement in PA context.